Extracting User Interests on Facebook. (29th June 2014) - Kim, Jeongin; Choi, Dongjin; Ko, Byeongkyu; Lee, Eunji; Kim, Pankoo
Abstract : Recently, through the rapid development of smart devices, Facebook has been publicly recognized as a representative social network service. Facebook has profile information that is the basis to form network relationship between people as well as closed information sharing between users. Also, social plug-in "Like" is a feature that Facebook includes. Current researches based on Facebook have a problem of not considering this "Like" feature. This paper has proposed the method of extracting user's interest by using Term Frequency of nouns and "Likes." "Posts" and "Likes" were collected through Facebook Open API. Collected "Posts" were preprocessed and Term Frequency of nouns was calculated. After calculating weights of user interests by using Term Frequency of nouns and "Likes, " user interests were extracted by higher ranked user interests weighting.